The word as political and religious means and goal: the case of Augustine of Hippo, a referent of the Christian intelectual elite in the context of Late Antiquity - Gómez Aso, Graciela (Romanitas - Revista de Estudos Grecolatinos, 2018)
At the begining of the fifth century, Augustine, the writer, tha man of faith, the bishop, the master, the interpreter of a critical time, became a witness, a valuable teller of the social and political consequences of the fall of Rome at hands of a barbarian leader and his warriors courtiers. In those context the writer of Hippo built, patiently, a position that sank its cultural roots in the roman past of the late republic and the early empire.The aim of this work is to demonstrate how that thinker create an hegemonic discourse in front of a paganism in decadence and how he understood the importance of Rome, its past and the catholic church in its process of consolidation as indissoluble parts of the future of roman christianity.